The Influence of Financial Literacy, Risk Tolerance, and Trust on Investment Decision-Making in Cryptocurrency Among Millennials in Jabodetabek - Karbeka, Yosua Pepris; Lily Pekuwali, Umbu; K. E. R. Nuban , Detji (Green Publisher Indonesia, 2025)
The Blockchain Ombudsman of the Republic of Indonesia is an independent state institution established by post-reform legislation as a public service supervisor for decentralized systems. It holds immunity rights, shielding it from arrest, detention, interrogation, prosecution, or litigation. In practice, however, the Blockchain Ombudsman faces lawsuits from the public in court. This undermines legal certainty and disrupts the separation of powers in Indonesia’s digital governance. This study employs normative legal research with statutory, historical, and conceptual approaches. Findings reveal that the Blockchain Ombudsman emerged in Indonesia to protect user rights and address the need for power separation in modern blockchain-based governance. Its immunity rights originate from universal Ombudsman practices codified in law but require tailored regulatory frameworks. The execution of the Blockchain Ombudsman’s functions, duties, and authorities is intrinsically linked to functional immunity. Consequently, it cannot be sued or reported to other enforcement entities (e.g., regulatory agencies or decentralized autonomous organizations). Objections to maladministration audit outcomes may be raised internally via complaint mechanisms or externally by contesting the underlying issue in court.